NIAT MENURUT HADIS DALAM PENGAMALAN BELAJAR MAHASISWA: Studi Kasus UIN Sunan Gunung Djati Bandung - Zahrotun Nisa; Wahyudin Darmalaksana (IJoIS: Indonesian Journal of Islamic Studies, 2021)
Abstract. This study aims to discuss the hadith about intention in student learning. This research applies qualitative research through literature and field studies with multi-methods and ethnographic approaches as well as content analysis. The results of this study indicate that almost all students know and understand the hadith about intention well, they also understand the importance of intention in learning, and they can feel a different inner atmosphere when learning is accompanied by intention with learning without intention. This study concludes that student learning success depends on intention through a continuous process of intention rehabilitation according to the hadith demands in achieving learning goals. This study recommends the need for some kind of rehabilitation institute intent on Islamic higher education.